UNIT 22.20 Mapping Replication Origin Sequences in Eukaryotic Chromosomes. Issue 1 (1st December 2014) - Fu, Haiqing; Besnard, Emilie; Desprat, Romain; Ryan, Michael; Kahli, Malik; Lemaitre, Jean‐Marc; Aladjem, Mirit I.
Abstract : Recent advances in genome‐sequencing technology have led to the complete mapping of DNA replication initiation sites in the human genome. This thorough origin mapping facilitates understanding of the relationship between replication initiation events, transcription, and chromatin modifications, and allows the characterization of consensus sequences of potential replication origins. This unit provides a detailed protocol for isolation and sequence analysis of nascent DNA strands. Two variations of the protocol based on non‐overlapping assumptions are described below, addressing potential bias issues for whole‐genome analyses. © 2014 by John Wiley & Sons, Inc.